Power Relations in Utilizing Public Space as a Parking Place in the Tunjungan Street, Surabaya - Khamimiya, Aza Rifda; Handoyo, Pambudi (Forum Ilmu Sosial, 2023)
Urban areas are areas with the largest population due to urbanization. As a result, problems arise. The problem that often occurs is the problem of using public space. As the population increases, the number of vehicles increases, so many parking spaces are used in public spaces due to the density that occurs in public space areas. So the context of power is often ignored in this case. The aim of the research is to find out how power relations and social capital are used by parking attendants in the Tunjungan street area. The method used is qualitative descriptive based on primary data. Primary data comes from documentation, observations and interviews with parking attendants. The selection of informants was carried out using a purposive sampling technique with a total of 5 parking attendants. The location chosen was in the area of Tunjungan street. Data collection was carried out in three stages, namely the reduction stage, data presentation and conclusion drawing. The results obtained are the power relations that are formed here, which are meant when there is social capital in the form of social networks owned by individual actors or groups in relation to other parties who have power. The relationship that exists between parking attendants and the government is based on a cooperation contract. Meanwhile, the causal relationship that is formed between parking attendants in determining areas is due to the power factor in the form of kinship.